Governanças contratuais e complementaridades das usinas pneumáticas na aquisição da borracha natural no estado de São Paulo - Pinotti, Raquel Nakazato (Universidade Federal de São Carlos, 2014)
Difficulties in supplying the raw material, coagulated latex, to processing plants of natural rubber from São Paulo are very present in this productive activity. The rubber industry also presents such scarcity problem with the supply of the natural rubber raw material, the GEB (Granulado Escuro Brasileiro). This scenario has always been present in the history of the natural rubber chain, having had, in some periods, the intervention of the State through public policies and the obligation to heveiculture fomentation by the rubber industry. The state of São Paulo is the biggest natural rubber producer, with the largest area of rubber tree plantation, in Brazil and it also concentrates a major part of processing plants. The thesis main objective is to analyze the processing companies (plants and rubber industries) transactions of natural rubber with their suppliers in the state of São Paulo. In order to achieve such objective, a characterization was carried out of the business attributes of the governance structure adopted by processing companies to ensure their raw material supply. The theoretical framework of the New Institutional Economics (NIE) and the Transaction Cost Economics (TCE) were also used. The understanding of the transactions carried out by the processing units in the raw material (coagulated latex) acquisition involves the description of the productive chain, the characterization of the institutional environment, the characteristics of the transaction and governance structures which are adopted by the processing companies located in the state of São Paulo. Agents of the rubber sector, plants, rubber industries and rubber producers were interviewed for such analysis in order to compose the institutional environment. The interviews resulted in five case studies (four plants and one rubber industry), which adopt forms of governance adaptive structures with their suppliers of the natural rubber. The transaction attributes of the processing companies with their suppliers are featured by: incomplete information (scarce or little information exchange), presence of uncertainty, an asset specificity (physical and dedicated to production), average frequency and price variation. The major presence of informal agreements and a mechanism of additions to the contract in the transaction are, mainly, guided by trust, reputation and authority. The analysis carried out showed that the transactions of the natural rubber supply for processing companies are ruled by mechanisms which are more complex than the TCE contracts. The presence of a high level of investment in specific assets, both in the heveiculture and in the processing, force agents into an approach and a long term relationship. In order to reduce the uncertainly in this economic activity, processing companies search for more than one way of governance representing a lower dependence of one supplier.
Keywords: Organização industrial (Teoria econômica); Estruturas de governança; Economia institucional; Borracha natural; Agroindústria; ENGENHARIAS::ENGENHARIA DE PRODUCAO